If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-49+6x=101+11x
We move all terms to the left:
-49+6x-(101+11x)=0
We add all the numbers together, and all the variables
6x-(11x+101)-49=0
We get rid of parentheses
6x-11x-101-49=0
We add all the numbers together, and all the variables
-5x-150=0
We move all terms containing x to the left, all other terms to the right
-5x=150
x=150/-5
x=-30
| 3n-7=40 | | 3x+x+21=x+9+5x | | 521/40=g | | -5+7t=7t+2 | | 3(s+5)=-2(3+9s) | | w+16=321 | | 50x+4=370 | | 7h−5h=14 | | 3x/4+11x/6=31/6 | | Y÷3+2x=70 | | N÷9-5n÷18=1÷9 | | 2(2x-3)=3x+10 | | 3k-2=46 | | 235.63+26.72=52.47d | | 2t=96 | | y−1/3y+7=10/1 | | y−1/3y+7=10/1 | | –3(4n–8)=–36 | | -8x-28=68 | | 8(8x-3)+2=-278 | | 29u=-406 | | -10=-4/n+7 | | 20+5y=9y | | -4x+(x)^2=0 | | y−1/3y+7=101 | | 11/a=2.2 | | x={20±√(400–168)}/6 | | p-2.97=17.97 | | -3x-85=-7 | | 3x²–20x+14=0 | | 9.4=2x+1.2 | | 38=-2(3a-4)-7(4a-8)−38=−2(3a−4)−7(4a−8) |